The Role of Human Resource Management in Institutional Effectiveness: A Comparative Study of Two Ghanaian Universities (Journal of Educational Management, 2023)
This paper examined the role of human resource management in institutional effectiveness. The objectives were to examine innovative strategies adopted by two public universities in Ghana to promote effectiveness in human resource management as part of the quality assurance strategies of such universities and compare the various systems used in managing human resources in both institutions. Using a comparative qualitative case study research design through semi-structured interviews and content analysis, the study found that both institutions did not have comprehensive (stand-alone) human resource (HR) policies to guide everyday HR practices however, separate policies existed for specific HR functions. Again, KNUST has a decentralised section for specific units but UENR operates a centralised human resource division. The study found that both institutions did not have strong systems for conducting HR audits. The study recommends that universities put structures and mechanisms in place to ensure continuous organisational feedback, perform a functional audit and design systems for assessment of HR policies to ensure that they are responsive to institutional/national laws and policies and promote effectiveness.
Keywords: Quality Assurance; Human Resource Audit; Performance Management System; Reward Management; Institutional Effectiveness; Institutional Growth